Frequency of CCR5?32 Variant in North-West of Iran - D. Omrani (Journal of Sciences, Islamic Republic of Iran)
Chemokine and chemokine receptors show several variations which may affect resistance to infectious disease. A 32 base pair deletion in the open reading frame of the human CCR5 gene (CCR5?32) results in producing a truncated antigen which fails to be presented on the surface of target cells. CCR5?32 variant is not a functional co receptor for HIV-1 entrance and delay the onset of acquired immunodeficiency syndrome. To determine the situation of Iranian population, regarding having this protective mutation in their CCR5 gene or not, this study was carried out. Genomic DNA was extracted using the salting out method from 190 healthy subjects. Using PCR method, the allelic and genotypic frequencies were found for this locus in the CCR5 gene. The results of this study showed that the frequency of the CCR5?32 allele in heterozygote form is about 0.0211. Also no homozygote form of the mutated CCR5 gene (?32/?32) was identified. Based on the findings of this study it is possible to say, Iranian nation compare to European nation are more susceptible to HIV virus infection during exposure to this virus. But to confirm this hypothesis, more investigation needs to be designed and performed.